2002
DOI: 10.1260/02636170260504341
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of Cationic Dyes by Cement Kiln Dust: Sorption Mechanism and Equilibrium Isotherm

Abstract: The mechanistic aspects of the sorption of Basic Blue-3 and Basic Red-22 on to cement kiln dust (CKD) have been investigated. The bypass kiln dust before and after washing with water was characterized by X-ray diffraction methods, IR spectroscopy and elemental analysis. Two forms of bypass kiln dust were used in this study without any treatment, i.e. in powder and pelletized form (the latter being achieved using water or sodium silicate). Equilibrium isotherms to assess the maximum capacity of the two basic dy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Red mud was also activated for increasing effectiveness of phosphorus removal behaviour (Pradhan et al 1998). Studies showed that cement kiln dust can be an effective adsorbent for other types of contaminants (Fadali et al 2004;Nassar et al 2002;Mikhail et al 2002;Smith and Campbell 2000), however, it was never tested as a phosphorus adsorbent.…”
Section: Introductionmentioning
confidence: 99%
“…Red mud was also activated for increasing effectiveness of phosphorus removal behaviour (Pradhan et al 1998). Studies showed that cement kiln dust can be an effective adsorbent for other types of contaminants (Fadali et al 2004;Nassar et al 2002;Mikhail et al 2002;Smith and Campbell 2000), however, it was never tested as a phosphorus adsorbent.…”
Section: Introductionmentioning
confidence: 99%
“…first section of plot, second section of plot third section of plot, good fits to the experimental data can be observed. This method was used by different researchers as reported in the literature whereby it has been divided up into sections (El-Geundi et al 2005, Wong et al 2003, Nassar et al 2002. For this reason the Freundlich constants had to be changed, in terms of equation ( 8), to obtain a good representation of the data over the entire concentration range.…”
Section: Freundlich Isothermmentioning
confidence: 99%
“…Some natural materials not only have excellent adsorbability of dyes, but also have biocompatibility, biodegradability, and nontoxicity. To replace activated carbon with cheaper alternatives such as natural materials mentioned above, and to utilize various waste products, many novel materials have been tested such as micro-organisms (Aksu, 2001;Aksu & Tezer, 2000;Basibuyuk & Forster, 2003;Hu, 1992;Mohan et al, 2002), tree fern (Ho, Chiang, & Hsueh, 2005), banana pith (Namasivayam & Kanchana, 1992;Namasivayam, Prabha, & Kumutha, 1998), neem sawdust (Khattri & Singh, 2000), peat (Poots, McKay, & Healy, 1978), agricultural waste residues (Robinson et al, 2002), recycled alum sludge (Chu, 2001), Fuller's Earth (Atun, Hisarlı, Sheldrick, & Muhler, 2003), lignite (Allen & Brown, 1995), perlite (Dogan, Mahir, & Onganer, 2000), apple pomace and wheat straw (Robinson et al, 2002), bottom ash and de-oiled soy (Gupta, Mittal, Krishnan, & Mittal, 2006;Low, Lee, & Tan, 1995), carbon slurry waste (Jain, Gupta, & Suhas, 2003), bamboo dust, coconut shell, groundnut shell and rice husk (Kanan & Sundaram, 2001), coir pith (Namasivayam et al, 2001), orange peel (Namasivayam, Muniasamy, Gayathri, Rani, & Ranganathan, 1996), Indian rosewood sawdust (Garg, Amita, Kumar, & Gupta, 2004), chitosan and chitin (Juang, Tseng, Wu, & Lin, 1996), biogas residual slurry (Namasivayam & Yamuna, 1992), activated carbon prepared from plum kernels (Wu, Tseng, & Juang, 1999), fly ash (Wang, Boyjoo, & Choueib, 2005), kaolinite (Ghosh & Bhattacharyya, 2002), calcinated alumite (Ozacar & Sengil, 2002), cement kiln dust (Nassar, ...…”
Section: Introductionmentioning
confidence: 99%